Urinary Tract Infection in Randomized Phase III Studies of Canagliflozin, a Sodium Glucose Co-Transporter 2 Inhibitor. Issue 1 (January 2014) - Nicolle, Lindsay E.; Capuano, George; Fung, Albert; Usiskin, Keith
Abstract: Background: Canaglifozin, a sodium glucose co–transporter 2 inhibitor, lowers plasma glucose in individuals with hyperglycemia by inhibiting renal glucose reabsorption and increasing glucosuria. Urinary tract infections (UTIs) were characterized in patients with type 2 diabetes mellitus enrolled in Phase III studies of canaglifozin.Methods: Analyses were performed in 2 pooled datasets: Population 1 (N = 2313; mean exposure [weeks]: canaglifozin, 24.3; placebo, 23.8) including patients from 4 placebo–controlled studies; Population 2 (N = 9439; mean exposure [weeks]: canaglifozin, 68.1; control, 64.4) including patients from 8 placebo– and active–controlled studies (including patients with renal impairment or high risk of cardiovascular disease, and older patients). Individual studies in special patient populations and 2 active–controlled studies were analyzed separately. Patients with a prior history of UTIs were not excluded from these studies. Urinary tract infection frequency and characteristics were systematically collected, with additional information for each event collected using supplemental electronic case report forms.Results: In Populations 1 and 2, canaglifozin 100 and 300 mg were associated with small increases in the incidence of UTIs compared with control, with no dose–dependence. Urinary tract infections with canaglifozin were similar to those with control in severity, and upper UTIs were infrequent across groups. No increase in serious events or those leading to discontinuation were seen with canagliflozin versus control. Time to the first occurrence of symptomatic UTIs tended to be earlier with canagliflozin than placebo in Population 1, and similar with canagliflozin and control in Population 2; median duration of events was similar across groups in both populations. The proportion of patients with recurrent events was low across groups.Conclusion: Canagliflozin was associated with a small increase in incidence of UTIs in patients with type 2 diabetes mellitus, with no increase in serious or upper UTIs.